1997
DOI: 10.1073/pnas.94.7.2833
|View full text |Cite
|
Sign up to set email alerts
|

A direct comparison of helix propensity in proteins and peptides

Abstract: ABSTRACT␣-Helical secondary structure occurs widely in globular proteins and its formation is a key step in their folding. As a consequence, understanding the energetics of helix formation is crucial to understanding protein folding and stability. We have measured the helix propensities of the nonpolar amino acids for an ␣-helix in an intact protein, ribonuclease T 1 , and for a 17-residue peptide with a sequence identical to that of the ␣-helix in the protein. The helix propensities are in excellent agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
123
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 45 publications
14
123
1
Order By: Relevance
“…Therefore, it seems likely that solvation differences play an important role in determining both the rank order and magnitude of helix propensities in 40% TFE. A similar conclusion was reached in comparing the two peptide systems in water (Myers et al, 1997a(Myers et al, , 1997b. Our comparison of propensity scales in water revealed that reasonable qualitative agreement exists between propensities measured in various systems (Myers et al, 1997a(Myers et al, , 1997b.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, it seems likely that solvation differences play an important role in determining both the rank order and magnitude of helix propensities in 40% TFE. A similar conclusion was reached in comparing the two peptide systems in water (Myers et al, 1997a(Myers et al, , 1997b. Our comparison of propensity scales in water revealed that reasonable qualitative agreement exists between propensities measured in various systems (Myers et al, 1997a(Myers et al, , 1997b.…”
Section: Discussionsupporting
confidence: 82%
“…A similar conclusion was reached in comparing the two peptide systems in water (Myers et al, 1997a(Myers et al, , 1997b. Our comparison of propensity scales in water revealed that reasonable qualitative agreement exists between propensities measured in various systems (Myers et al, 1997a(Myers et al, , 1997b. This allowed an experimentally based consensus scale of helix propensities to be derived (Pace & Scholtz, 1997).…”
Section: Discussionsupporting
confidence: 73%
“…k, which represents the minimum number of helical residues required to produce the CD signal, is an empirically determined constant that ranges from 3 to 4.3 (23,24). We adopted the value of 3 (23).…”
Section: Methodsmentioning
confidence: 99%
“…k, which represents the minimum number of helical residues required to produce the CD signal, is an empirically determined constant that ranges from 3 to 4.3 (23,24). We adopted the value of 3 (23). [ ] helix , which represents the mean residue ellipticity of a complete helix, is given by Ϫ42,500(1Ϫ 3͞N r ) (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation